Genetic variability and characters association for yield, yield attributing traits and protein content of lentil (Lens Culinaris Medikus) genotype in Ethiopia - Emebet Takele; Firew Mekbib; Fikru Mekonnen (CABI Agriculture and Bioscience)
Abstract Background Lentil is a multipurpose annual legume crop grown in many environments of Ethiopia and recognized as the second center of diversity in the country. However, there is limited information on genetic variation, association of yield, yield-attributing traits, and protein content of lentil in the country. Therefore, this study was conducted to assess the genetic variability, traits association, direct and indirect effects of yield-related traits and protein content on seed yield of lentil genotypes. Methods A total of 64 lentil genotypes were evaluated for morpho-agronomic traits and protein content in an 8 × 8 simple lattice design at Debre Berhan Agricultural Research Center in 2018. Results The analysis of variance displayed significant differences among the genotypes for all traits indicating the existence of variability and potential for selection of the genotypes for desirable traits. High heritability and high genetic advance were observed for seed yield (96.57%, 81.32%), above-ground biomass (79.03%, 57.99%), days to 50% flowering (70.97%, 23.17%), and the number of seeds per pod (69.41%, 38.23%), respectively. High heritability and moderate genetic advance were detected in plant height (62.63%, 19.77%) and protein content (73.2%, 17.13%), respectively. A positive and significant correlations was observed in phenotypic and genotypic levels of seed yield and above-ground biomass (r = 0.90, 0.93), number of seed per pods (r = 0.79, 0.85), number of pods per plant (r = 0.52, 0.64), plant height (r = 0.49, 0.55), harvest index (r = 0.38, 0.45), secondary branches (r = 0.48, 0.56) and protein content (r = 0.24, 0.26), respectively. Above-ground biomass, harvest index, secondary branches, plant height, number of pods per plant, and protein content were exerted positive and direct effect on yield at phenotypic and genotypic level. This suggested that seed yield, above-ground biomass, harvest index, number of pods per plant, number of seed per pod, plant height, secondary branches, and protein content are the most important traits in selection of lentil improvement. Conclusion The study results showed that the presence of wide range of genetic variations among lentil genotypes with desirable traits in above-ground biomass, harvest index, number of pods per plant, number of seeds per pod, plant height, seed yield, and protein content. This variation among traits could be used to develop varieties through selection and hybridization for lentil seed improvement.